Decision to delivery intervals for grade 1 and 2 ceasarean sections. (7th June 2011) - Graham, N; Shawkat, E; Gillham, J
Abstract : Introduction: There are a number of different recommended decision to delivery times. Method: Retrospective study of all breached grade 1 and 2 caesarean sections in a 6 month period. Results: 2690 deliveries, 546 caesarean sections; of which 185 were grade 1 and 137 grade 2. 8.1% grade 1 sections and 14.6% grade 2 sections breached. Mean decision to delivery interval (DDI) was 36.7 min for grade 1 and 103.3 min for grade 2. When looking closer the main areas for delay were transporting the patient to theatre and anaesthetic delays. 40% of the breached grade 2 sections had 'theatre already in use' as the main delay. There was no difference between the groups neonatal outcomes with equal numbers needing SCBU admission and Apgar's <8 and 5 min, however neonates in the grade 1 group had a higher percentage of low cord gasses (50% v.21%). Maternal outcomes were similar. A number of the breached cases occurred during staff handover times, time of day did not have any effect. Conclusion: As the units delivery numbers increase the delay in waiting for a theatre will worsen. Good communication between all staff is vital. Patient needs to be out of the room within the first 10 min to achieve the recommended DDI. A larger study is needed looking at all grade 1 and 2 caesarean sections.